RESPECTING PRINCIPLE IN DUBIO PRO VITA IN DECISIONING ON THE RIGHT TO REIMBURSEMENT OF TREATMENT COST - Jovanović, Marina (Glasnik Advokatske komore Vojvodine, 2020)
In the procedure of deciding on the right to reimbursement of medical treatment costs, which is conducted in the first and second instance before the competent bodies of the Republican Health Insurance Fund, as well as in the procedure before the Administrative Court competent to decide the final acts of the Fund, decisions are made primarily through examination of fulfillment of the formal conditions related to the manner and exercise of the right to health care prescribed by the Health Insurance Law and the Rulebook on the manner and procedure for exercising the rights from compulsory health insurance. Experience has shown that, in the above procedures, due attention is not paid to one of the basic principles of medical ethics IN DUBIO PRO VITA (in doubt, for life), which is legally enshrined in the principle of respect for life (right to life) proclaimed by Article 24, paragraph 1, of the Constitution of the Republic of Serbia. The topic will be addressed with a representative law case and the legal attitude expressed in the judgment of Administrative Court U.4079 / 13 of 14.11.2014. in which, in deciding the right to reimbursement, the rigid legal procedure outweighed the principle of respect and integrity of life. Doubt should not go beyond the strict wording of lower legal acts, but the right to reimbursement of treatment costs should be valued according to the highest legal act in the country, international declarations to which we are signatories and general principles of law.
Keywords: in dubio pro vita, principles, life, health, legal regulation